1985
DOI: 10.1038/313144a0
|View full text |Cite
|
Sign up to set email alerts
|

Amplification, enhanced expression and possible rearrangement of EGF receptor gene in primary human brain tumours of glial origin

Abstract: Epidermal growth factor (EGF), through interaction with specific cell surface receptors, generates a pleiotropic response that, by a poorly defined mechanism, can induce proliferation of target cells. Subversion of the EGF mitogenic signal through expression of a truncated receptor may be involved in transformation by the avian erythroblastosis virus (AEV) oncogene v-erb-B, suggesting that similar EGF receptor defects may be found in human neoplasias. Overexpression of EGF receptors has been reported on the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
615
0
8

Year Published

1986
1986
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,398 publications
(635 citation statements)
references
References 24 publications
10
615
0
8
Order By: Relevance
“…28 Further, activation of the Figure S6D). Furthermore, the siRNA-mediated downregulation of EGFR resulted in significantly reduced colony formation in a clonogenicity assay (Supplementary Figure S7) suggesting that Notch1-mediated EGFR regulation contributes to the Notch1-dependent modulation of proliferation.…”
Section: Notch1 Regulates Mcl-1 Through Modulation Of Egfr Expressionmentioning
confidence: 96%
“…28 Further, activation of the Figure S6D). Furthermore, the siRNA-mediated downregulation of EGFR resulted in significantly reduced colony formation in a clonogenicity assay (Supplementary Figure S7) suggesting that Notch1-mediated EGFR regulation contributes to the Notch1-dependent modulation of proliferation.…”
Section: Notch1 Regulates Mcl-1 Through Modulation Of Egfr Expressionmentioning
confidence: 96%
“…Results were also separately con®rmed using scanning densitometry. In U87MG cells, the EGFr is overexpressed and appears to mediate the transformed phenotype (Libermann et al, 1985;Nishikawa et al, 1994). In U87/T691 cells, the T691stop mutant proteins heterodimerize with the EGF receptor, suppressing transformation characteristics of these tumor cells (O'Rourke et al, 1997).…”
Section: Subcellular Localization Of the P215 Brca1 Polypeptidementioning
confidence: 99%
“…Exceptions to this observation include gliomas and squamous cell carcinomas, which show amplification of EGFR. 8 While in some studies EGFR expression has been correlated with markers of clinical aggression, 9-11 a recent meta-analysis indicated that EGFR expression was rarely related to clinical outcome. 12 Yet another study suggested that phosphorylation of EGFR, but not its overexpression, might be associated with a poor prognosis.…”
mentioning
confidence: 99%